The Role of Absorptive Capacity in the Relationship FDI and Economic Growth: A Case Study of Binh Dinh Province, Viet Nam - Thuy. N.T.T (My University, 2019)
The Role of Absorptive Capacity in the Relationship FDI and Economic Growth: A Case Study of Binh Dinh Province, Viet Nam
Keywords: Absorptive Capacity; FDI; Economic Growth